Quadruple space-group ambiguity owing to rotational and translational noncrystallographic symmetry in human liver fructose-1,6-bisphosphatase - Ruf, Armin (International Union of Crystallography, 2016)
The crystal structure of the liver isoform of human fructose-1,6-bisphosphatase in the active R-state conformation was determined by molecular replacement using data from a crystal with noncrystallographic rotational symmetry and pseudo-translation. Owing to an almost perfect placement of noncrystallographic symmetry elements, quadruple space-group ambiguity within the same Laue symmetry arises, including two enantiogenic pairs. The origins of space-group ambiguity, the assignment of the correct space group, refinement and model properties are discussed.